Impact of Corneal Arcus on the Sealing of Clear Corneal Incisions in Cataract Surgery - Yoshida M; Hashizume K; Imaizumi T; Hashiura T; Kurosaka D (Clinical Ophthalmology)
Mizuho Yoshida,1,* Kouhei Hashizume,1,2,* Toshiyasu Imaizumi,1 Tetsuya Hashiura,1 Daijiro Kurosaka1 1Department of Ophthalmology, School of Medicine, Iwate Medical University, Shiwa-gun, Iwate, Japan; 2Department of Ophthalmology, Ichinoseki Hospital, Ichinoseki, Iwate, Japan*These authors contributed equally to this workCorrespondence: Daijiro Kurosaka, Department of Ophthalmology, School of Medicine, Iwate Medical University, Shiwa-gun, Iwate, Japan, Tel +81 19 651 7111, Fax +81 19 653 2864, Email kurosaka@iwate-med.ac.jpPurpose: To determine whether the corneal arcus affects sealing of the clear corneal incision (CCI) in cataract surgery.Patients and Methods: This study was a retrospective cohort study. The patients were divided into two groups based on whether stromal hydration was required to close the CCI. The corneal arcus was classified according to its degree as none, partial (if corneal arcus < 180 degrees), and circumferential (if corneal arcus ≥ 180 degrees). Multiple logistic regression was conducted to identify independent variables such as age at cataract surgery, sex, laterality, surgical time, and degree of corneal arcus associated with CCI sealing.Results: Among a total of 83 eyes of 83 patients, a partial corneal arcus was found in 34 eyes (41.0%) and a circumferential arcus in 33 eyes (39.8%). Multiple logistic regression analysis revealed that the need for stromal hydration in wound sealing increased with surgical time (OR = 1.7313, 95% CI = 1.1500– 2.6063, p = 0.0085) and decreased with severity of corneal arcus (partial, OR = 0.2901, 95% CI = 0.0451– 1.8665, p=0.1926; circumferential, OR = 0.0590, 95% CI = 0.0074– 0.4722, p = 0.0085); age was not associated (OR = 0.9790, 95% CI = 0.9121– 1.0507, p = 0.5555).Conclusion: Eyes with corneal arcus required less stromal hydration. This finding suggests that corneal arcus may increase CCI sealing in cataract surgery.Plain Language Summary: Corneal arcus is found in elderly persons, but its significance is unknown. Eyes with corneal arcus required less stromal wound hydration in cataract surgery. Corneal arcus may contribute to the closure of a clear corneal incision.Keywords: clear corneal incision, cataract surgery, corneal arcus